(untitled) (Canadian Perspectives on Academic Integrity, 2022)
“Academic integrity in Canada: an enduring and essential challenge” is an open-access book recently published by Springer as part of the series “Ethics and Integrity in Educational Contexts”. Edited by scholars Sarah Elaine Eaton and Julia Christensen Hughes, it contains over 600 pages in 31 chapters designed to address the gap in Canada’s study and evidence-based recommendations involving academic integrity. The book is divided into five sections: Canadian context, emerging and prevalent forms of academic misconduct, integrity within specific learning environments and professional programs, barriers and catalysts to academic integrity: multiple perspectives and supports, and institutional responses. In this moderated panel session, several chapter authors as well as Sarah Elaine Eaton will delve into specific aspects of their contributions towards the book. Through the open question and discussion segment, attendees will be inspired to contribute in their own institutional roles towards provincial and, ultimately, the growing Canadian academic integrity community. Learning Outcomes • Discuss academic integrity culture and initiatives in Canada • Identify ways to make contributions towards academic integrity in various roles and institutions • Reflect on specific aspects of academic integrity covered in individual chapters